2020
DOI: 10.1017/cem.2019.471
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone dosing in the era of ultra-potent opioid overdoses: a systematic review

Abstract: ObjectivesEvaluate the relationship between naloxone dose (initial and cumulative) and opioid toxicity reversal and adverse events in undifferentiated and presumed fentanyl/ultra-potent opioid overdoses.MethodsWe searched Embase, MEDLINE, Cochrane Central Register of Controlled Trials, DARE, CINAHL, Science Citation Index, reference lists, toxicology websites, and conference proceedings (1972 to 2018). We included interventional, observational, and case studies/series reporting on naloxone dose and opioid toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…At program inception each THN kit contained two naloxone ampoules. In response to the rise of ultra-potent synthetic opioids on the illicit market, and evidence suggesting a need for higher naloxone dosing [27,28], a third ampoule was added to the kits in March 2016. We determined the health region by recoding the city or community where the overdose occurred.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…At program inception each THN kit contained two naloxone ampoules. In response to the rise of ultra-potent synthetic opioids on the illicit market, and evidence suggesting a need for higher naloxone dosing [27,28], a third ampoule was added to the kits in March 2016. We determined the health region by recoding the city or community where the overdose occurred.…”
Section: Plos Onementioning
confidence: 99%
“…McDonald and Strang also consolidated data on adverse events, and report 65 instances of withdrawal symptoms for the 2336 naloxone administrations included a rate of 2.8%. A recent systematic review by Moe et al 2020 [27] found that 11% of individuals experienced withdrawal, and 1% experienced pulmonary edema, after naloxone administration in community settings or emergency departments. Our study reported a higher estimate compared to Moe et al and McDonald & Strang; 15.4% of the sample reported moderate or severe withdrawal [27,37] In most BC health regions, the number of naloxone ampoules administered increased over time.…”
Section: Plos Onementioning
confidence: 99%
“…Increasing the standard dose of naloxone is also warranted because overdoses involving synthetic opioids like fentanyl and fentanyl analogues often require more naloxone to reverse. (47, 48)…”
Section: Discussionmentioning
confidence: 99%
“…We identified five systematic reviews focused on comparing the effectiveness between injectable (e.g., intravenous, subcutaneous, intramuscular) and noninjectable (e.g., intranasal, buccal, sublingual) naloxone routes of administration [30,39,40,42,44]. A final systematic review published in 2020 aimed to evaluate sufficient naloxone doses during an era of ultra-potent synthetic opioid use [39].…”
Section: Naloxone Dosing and Route Of Administrationmentioning
confidence: 99%